PENERAPAN WATERFALL SDLC PADA PERANCANGAN SISTEM PENGELOLAAN IZIN KELUAR KANTOR DI KANREG VI BKN MEDAN - Aznawi, Nasrul Mahruf; Fachroza, Siti Dian; Ermaliza; Ritonga, Dedek Juliani; Suhardi (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2026)
The handling of office leavepermits at the Regional Office VI of the State Civil Service Agency (BKN) in Medan is still done manually, causing various problems such as delays in approval, lack of transparency, potential data manipulation, and the unavailability of well-documented employee permit histories. This condition has a direct impact on work effectiveness and the accuracy of personnel administration. This study aims to design and develop a web-based office leave management system to improve the efficiency and transparency of the administrative process. The system development method used is the Software Development Life Cycle (SDLC) with the Waterfall model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. Data collection was carried out through observation and interviews to ensure that the system meets user needs. The results of the study show that the developed system is capable of managing the process of submitting, approving, and recording office leave digitally and in an integrated manner. System testing using the Black Box Testing method showed that all main functions ran according to system requirements. This system is capable of increasing the speed of the service process, reducing administrative errors, and providing a well-documented history of permits.